ENDOPHYTIC BACTERIA SCREENING FROM THE LEAVES OF OKRA (Abelmoschus esculentus L. Moench) WHICH PRODUCED LIPASE - Utami, Nanda Putri; Astuti, Winni; Kartika, Rudi (Jurusan Kimia FMIPA UNMUL, 2020)
Endophytic bacteria found in plant tissues can produce enzymes, one of which is lipase. The purpose of this study was to screening endophytic bacteria from the leaves of Okra (Abelmoschus esculentus L. Moench) which produced lipases. The method used in this study is screening with media nutrient agar (NA) containing Rhodamine B and olive oil. The results showed that 4 of bacterial isolates (D1, D2, D3 and D4) from 14 endophytic bacterial isolates had lipase activity. The crude lipase extract was quantitatively tested for lipase activity by the titrimetry method. The highest lipase activity was shown by isolates with a D1 code of 1.50 U/mL.